Trends and risk markers of student hazardous drinking: a comparative analysis using longitudinally linked datasets in a public university. Issue 6 (24th August 2022) - Holstege, Christopher; Ngo, Duc Anh; Borek, Heather; Ait-Daoud, Nassima; Davis, Susan; Rege, Saumitra
Abstract: Aims: This study compares the incidence and risk-markers of student alcohol intoxication-related emergency department (ED) visits and alcohol-related incidents reported to student affairs. Methods: Enrollment data were linked to ED visits with alcohol intoxication and to alcohol-related incidents reported to campus authorities within one year following the first (index) annual enrollment. Incidence, annual trends and associated risk markers were analyzed. Results: The cohort consisted of 204, 423 students aged 16–49. Incidence rates of first ED visit with alcohol intoxication and alcohol-related incidents were 59/10, 000 and 311/10, 000 person-years, respectively. Both outcomes shared common risk-markers including age, gender, race/ethnicity, fraternity and sorority (FSL) membership, an existing diagnosis of depression, etc. Being an athlete was associated with a lower risk of alcohol-related ED visits, and transfer students were at lower risk for alcohol-related incidents. Conclusion: Linking enrollment data with hazardous drinking events can help in better monitoring of student hazardous drinking and targeting interventions. Highlights: First longitudinal study documenting the incidence of extreme student alcohol misuse. There were rising trends in student risky drinking based on two independent datasets. Analysis identified a range of risk markers predictive of risky drinking behaviors. Linking multiple student datasets can timely identify high risk students.